Anatomy of a consultation. Unraveling patient-provider communication - Ellen Smets (European Health Psychologist, 2026)
Good communication between patients and their healthcare providers is widely regarded as essential for providing high-quality care. This raises the question of what constitutes ‘good’ communication. In this paper, I discuss how scholars have argued that good communication should be patient-centred and goal-oriented, and more recently, support shared decision-making. Using examples of research, I will then unravel ‘the anatomy’ of a consultation, illustrating what patient–provider communication actually looks like in clinical practice. I focus on information provision and decision-making, including some of the challenges that patients and providers face when trying to have a patient-centred, goal-oriented conversation. Additionally, I will demonstrate how communication can positively affect desired patient outcomes, such as patients’ memory of the information provided to them. Finally, I will discuss the possible implications of emerging health technologies for the interaction between patients and their providers.